2021
DOI: 10.1038/s41419-021-03959-3
|View full text |Cite
|
Sign up to set email alerts
|

HMGB2 orchestrates mitotic clonal expansion by binding to the promoter of C/EBPβ to facilitate adipogenesis

Abstract: High-mobility group box 2 (HMGB2) is an abundant, chromatin-associated protein that plays an essential role in the regulation of transcription, cell proliferation, differentiation, and tumorigenesis. However, the underlying mechanism of HMGB2 in adipogenesis remains poorly known. Here, we provide evidence that HMGB2 deficiency in preadipocytes impedes adipogenesis, while overexpression of HMGB2 increases the potential for adipogenic differentiation. Besides, depletion of HMGB2 in vivo caused the decrease in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Hence, we consider that SESN3 regulated pre-adipocyte adipogenesis through inhibiting its proliferation effect, and then further suppressing differentiation. There are some reports that also concur this idea: For instance, the inhibition effect of HMGB2 and KDM5 for pre-adipocytes thus suppressed adipogenesis [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 91%
“…Hence, we consider that SESN3 regulated pre-adipocyte adipogenesis through inhibiting its proliferation effect, and then further suppressing differentiation. There are some reports that also concur this idea: For instance, the inhibition effect of HMGB2 and KDM5 for pre-adipocytes thus suppressed adipogenesis [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 91%
“…Several factors and proteins regulate this process by interacting with C/EBPβ [ 46 ]. Very recently, a protein belonging to the non-histone chromosomal high mobility group protein family, the High Mobility Group Box 2 (HMGB2), has been studied in the early phase of adipogenesis.…”
Section: Novel Mechanisms Involved In Early Phases Of Adipogenesismentioning
confidence: 99%
“…The peak of expression of this protein is at 24 h after differentiation induction, while its expression decreases during the late stage. It was then observed that the HMGB2 knockdown, 72 h before adding adipogenic stimuli, impairs adipogenesis while the downregulation 48 h after the induction of adipogenesis does not affect terminal differentiation [ 46 ]. Thus, the mechanism by which this protein plays a role during the mitotic clonal expansion is through the binding to the C/EBPβ promoter, stimulating the transcription of factors essential for proper adipocytes differentiation.…”
Section: Novel Mechanisms Involved In Early Phases Of Adipogenesismentioning
confidence: 99%
See 2 more Smart Citations